Exploring The Influence Of Trust On Intention To Visit Bali: A Theory Of Planned Behavior Analysis - Miko Andi Wardana; I Wayan Eka Sudarmawan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aims to investigate the factors influencing domestic tourists' intention to visit Bali using the Theory of Planned Behavior (TPB) framework. Specifically, it focuses on the role of trust and its impact on subjective norms, attitudes, and perceived behavioral control in shaping tourists' intention. A cross-sectional survey was conducted using a structured questionnaire to collect data from 138 potential domestic tourists in Bali. The path analysis approach with Smart PLS was employed to analyze the relationships between trust, subjective norms, attitudes, perceived behavioral control, and intention to visit Bali. The results revealed that trust significantly influenced tourists' intention to visit Bali. Moreover, trust indirectly impacted intention through subjective norms, attitudes, and perceived behavioral control. Destination marketers and tourism stakeholders should prioritize building trust and promoting positive experiences to enhance tourists' perception of Bali. Addressing barriers and promoting positive social influence can further strengthen tourists' intention to visit, ultimately contributing to sustainable tourism growth in Bali.